A psychometrics evaluation of the Thai version of Caregiver Contribution to Self-Care of Chronic Illness Inventory Version 2 in stroke caregivers - Nuntaporn Klinjun; Jom Suwanno; Kannika Srisomthrong; Juk Suwanno; Matthew Kelly (Elsevier, 2023)
Objectives: To evaluate the psychometric characteristics of the Thai version of Caregiver Contribution to Self-Care (CC-SC) of Chronic Illness Inventory version 2 (CC-SC-CII-v2) in stroke caregivers. Methods: We conducted a multicenter, cross-sectional study following the COSMIN guidelines, evaluating validity and reliability of three separate scales, CC-SC Maintenance, CC-SC Monitoring, and CC-SC Management, as well as overall CC-SC-CII-v2. From September to December 2022, we enrolled 422 stroke caregivers from primary care centers in southern Thailand. Structural validity was assessed through confirmatory factor analysis (CFA), while concurrent validity was evaluated using Pearson's correlation r coefficients between CC-SC-CII-v2 and the Caregiver Self-Efficacy in Contributing to Patient Self-Care Scale (CSE-CSC). Internal coherence reliability was assessed using Cronbach's α coefficient, the composite reliability index, and the McDonald's ω coefficient. Additionally, test-retest reliability was assessed with intraclass correlation coefficients (ICCs). Results: The study included mostly middle-aged women who cared for their parent. CFA supported the two-factor structure of the CC-SC Maintenance and Management scales and the one-factor structure of the CC-SC Monitoring scale. A simultaneous CFA on the combined set of items supported the more general model. The concurrent validity of CC-SC-CII-v2 with CSE-CSC was established (r ranging 0.47-0.65, all P < 0.001). Reliability estimates supported adequate Cronbach's α coefficient (ranging 0.83-0.89), composite reliability (ranging 0.84-0.85), McDonald's ω coefficients (ranging 0.83-0.85), and ICCs (ranging 0.86-0.90) across the three scales. Conclusions: The Thai CC-SC-CII-v2 demonstrated strong psychometric properties among stroke caregivers. It can be a valuable instrument to investigate the role of caregivers in contributing to stroke patients' self-care in diverse cultural contexts like Thailand.